(3fU GdCNVQis - (3YHO GdQMef Hf eMeO GdUZjQ GdGNVQj, CHh RjO,J (B983 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3Chd eG jLH Ydi Gdecda JUMjM EjeGfg Ke eYQaI eG jUdM Hg bQV Yjfg s
(3BNQgG (B:s
(3aEPG Sde aRO QcYI CNQi HOdkG ef GdQcYI GdJi CdZjJgG LGfjkG hJSLO bHd GdSdGe s
(3GdeNWhWI HaccI heJBcdg ef GdCWQGa heTcdI HGdMLQ GdCMeQ hJfbU ef BNQgGs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B331s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3Gdabg GdeGdcjs